Management Substitution Patterns In The Current Era (International Journal of Applied Research in Management and Economics, 2018)
Human beings are central issues in management and organization. In today’s world, the knowledge-based economy is considered, and in this view, human resources are regarded as intellectual property, spiritual capital, and the most valuable capital of an organization. The proper management of human resources will increase productivity and positive economic outcomes. Due to the shortage of management forces and the increasing need for organizations for more capable and more skilled managers in the coming years, attention to management alternatives is essential for these needs. Management succession planning is one of the most important issues in the planning of human resources to fill the gaps and to meet the requirements of key and sensitive parts of the organization at the management level. In this paper, four main perspectives of management substitution patterns – education and empowerment, the basis of employee maturity, strong organizational culture, a delegation of authority and self-management – have been discussed and finally, a conceptual model of these perspectives (as article innovation) is extracted and is presented.